Maternal and fetal outcome in pregnancy with hepatitis E virus infection - Yadav, Sunil; Shirodker, Sneha; Kshirsagar, Swapnali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Hepatitis E infection has been a major concern in the pregnant females due to its fulminant nature in pregnancy and increased mortality in pregnant females as compared the non-pregnant females and males. In spite of approximately 60 years of its discovery the cause of fulminant nature of hepatitis E in pregnancy still remains a mystery. The maternal and fetal outcomes are still unfavorable. Various studies and hypothesis have been given but still not proved. Hence the study was performed in tertiary care centre to evaluate the maternal and fetal outcome in pregnancy with hepatitis E virus infection. Methods: All cases of hepatitis E, IgM positive visiting the antenatal clinic or admitted during the period of 2012 and 2014 at the tertiary care centre were included in the study. Other cases of hepatitis (noninfectious, other causes of viral hepatitis) were excluded. Maternal outcome in terms of acute liver failure, coagulation failure, hepatic encephalopathy and maternal mortality was studied. Fetal outcome in terms of, preterm labor, low birth weight, intrauterine fetal death was studied. Results: In the study it was found that pregnant women with jaundice and acute viral hepatitis due to hepatitis E virus infection had a high mortality rate (52%), especially during third trimester and postpartum period (82%). The most common medical complication was coagulation failure (56%) and acute liver failure (27%) followed by hepatic encephalopathy (17%). The most common obstetric complication was post-partum hemorrhage (42%) followed by IUFD (24%), APH (8%). Conclusions: The study shows that pregnant women with jaundice and acute viral hepatitis due to hepatitis E virus infection had a high mortality rate especially during third trimester and postpartum period and also they had poor obstetric and fetal outcome.